Molecular insights into the structural, spectroscopic, chemical shift characteristics, and molecular docking analysis of the carbamate insecticide fenobucarb - K. KrishnaKumar; M. Jenifer; T.J. Nandhini; M. Sridharan; G. Sabarinathan; Pallavi M. Shanthappa (Chemical Physics Impact)
In this study, fenobucarb a carbamate pesticide has been analyzed for its structural, spectroscopic (FT-IR and FT-Raman), electronic (UV–Vis.), chemical shifts (NMR) and topological, and bioactivity using the theoretical DFT technique. In optimized geometry, the computed bond distance of N3-H29 is reduced compared to other bond distances. This reduction is attributed by electron-with drawing in the carbonyl group. Carbon atoms C8 and C14 are bonded to single-bonded and double-bonded oxygen atoms, resulting in increased resonance signals at 157.87 ppm and 159.19 ppm, respectively, attributed to the oxygen atoms deshielding effects. NBO analysis computed increased stabilizing energy at 34.05 kcal/mol by electron-donating from lone pair (LP) oxygen (O2) to the antibonding O1-C14. The topological analysis emphasizes the shielding and deshielding regions within the molecular structure of fenobucarb. Molecular docking analysis revealed that fenobucarb forms hydrogen bonds and hydrophobic interactions with the target protein, exhibiting a binding energy of -5.75 kcal/mol, confirming its antibacterial activity.